Precisión de los criterios predictivos de la ASGE para el diagnóstico de Coledocolitiasis en pacientes atendidos en el Hospital Belén de Trujillo, 2017-2018 - Amador Morillo, Liliana (2019)
Choledocholithiasis (CL) is defined as the presence of stones (stones) in the bile ducts. Choledocholithiasis can be primary or secondary. The secondary form is the most frequent (8-20% of patients undergoing cholecystectomy, 2-4% post-cholecystectomy), and results from the migration of stones from the gallbladder. The gold standard for the diagnosis of choledocholithiasis is ERCP (93% sensitivity, 100% specificity) In 2010 the American Society for Gastrointestinal Endoscopy (ASGE) published a clinical guide defining clinical predictors and risk categories for choledocholithiasis. According to this clinical guideline, the presence of any “Very strong” predictor or both “Strong” predictors indicate an “High risk of choledocholithiasis” (> 50%), and these patients should have direct access to ERCP. Any other combination of predictors indicates an "Intermediate Risk of Choledocholithiasis," and these patients would benefit from less invasive studies such as EUS, MCPR, and introperative cholangiography (IOC) to assess the need for additional therapeutic action. The absence of risk predictors indicates a "Low risk of choledocholithiasis". Therefore, the objective set is to determine if there is precision of the predictive criteria of the ASGE for the diagnosis of Choledocholithiasis in patients treated at the Hospital Belén de Trujillo, between January 2017 and December 2018.